MANAGEMENT OF STUDENT COOPERATIVE-BASED EDUCATION FINANCING IN PUBLIC ELEMENTARY SCHOOLS - Reny Hajar Setyawati; Aulia’ul Fajriyah; Imelda Dian Rahmawati; Hidayatulloh (International Journal of Economic Integration and Regional Competitiveness, 2024)
The review of this research is motivated by education financing in the financing management of the Sidoklumpuk State Elementary School cooperative which can benefit the continuity of educational activities at the school. The purpose of this research is to find out the shape of the system for managing finance in the cooperative that can be benefited by the school community such as purchasing books, learning equipment, or repairing facilities and providing loans with low interest to students and staff for those who have financial difficulties. The method used is a qualitative method that focuses on the management of student cooperative-based education financing in public elementary schools. The research data used observation, interviews and documentation studies. The results of the study show that the benefits and implementation of financing in school cooperatives can be used well by school community.  If in the system there is a lack of understanding and managerial skills among students and school staff. Then training is needed for staff or teachers who are responsible so that it can be used with a good managerial system